(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, the implementation of simple and IoT based wireless notice board is presented. The proposed system uses Wi-Fi for communicating with cloud data base. The idea of digital notice board and it’s working starts from pushing a message to cloud using an android mobile. At the received end aArduino Uno with a valid internet connection is setup is deployed and it is ready to receive the messages. Whenever it receives a new message it alerts the LCD display connected to it and it displays the message on LCD display.